Credibility of government policy: Lessons for economies in transition - Norbert Funke (Intereconomics, 1993)
Reforms have to be credible in order to fully reveal the intended positive effects. This important lesson for economies in transition is illustrated by recent experiences in developing countries. The following article discusses several possible ways of enhancing credibility.
Keywords: 330; System Transformation